Review Policy of Archive Management at Cintajaya Village Office - Agung Febriansyah; Arip Budiman (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2026)
Archive management is an essential element of public administration because it supports administrative order, service effectiveness, institutional accountability, and public trust. At the village government level, archives function not only as administrative files but also as legal evidence, institutional memory, and a basis for transparent decision-making. This study aims to review the archive management policy at Cintajaya Village Office by examining the existing conditions, identifying policy gaps, and formulating an improvement direction for more systematic archive governance. The study employed a qualitative descriptive approach using secondary data through literature review and document analysis. The data sources consisted of academic literature, government regulations, policy documents, institutional reports, and relevant studies on records management, public accountability, digital archives, and village administration. The findings show that archive management at Cintajaya Village Office is still characterized by conventional administrative practices, incomplete indexing, fragmented physical and digital storage, delayed retrieval, weak retention control, and limited monitoring. These conditions indicate that archive management has not yet been fully integrated into a clear records lifecycle framework. The study also found that policy gaps occur in classification, storage, retention, access control, human resource capacity, and digital readiness. Therefore, archive management reform requires an integrated and adaptive policy model that combines policy standardization, lifecycle-based records management, hybrid physical-digital archive integration, staff capacity development, accountability mechanisms, and periodic monitoring. This study concludes that strengthening archive management policy at Cintajaya Village Office is necessary to improve public service responsiveness, reduce administrative risks, support evidence-based governance, and build a more accountable village administration system.